Reactive-site-centric chemoproteomics identifies a distinct class of deubiquitinase enzymes - David S. Hewings (Nature Portfolio, 2018)
Deubiquitinases are proteases that cleave after the C-terminus of ubiquitin to hydrolyze ubiquitin chains and cleave ubiquitin from substrates. Here the authors describe a reactive-site-centric chemoproteomics approach to studying deubiquitinase activity, and expand the repertoire of known deubiquitinases.